Did the ECB overstep its mandate? Assessing deflationary risks in the euro area - Ulrich Fritsche; Artur Tarassow (Intereconomics, 2015)
Recent price developments in the euro area demonstrate that deflation is a serious issue of concern. Some euro area countries are already facing a deflation in the usual macroeconomic sense of a 'general price decline'. This article discusses the economic consequences of deflation and suggests that the ECB's expansionary monetary policy was inevitable.
Keywords: 330; Deflation; Geldpolitik; EU-Staaten